2020
DOI: 10.1111/hel.12756
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Helicobacter pylori with nonalcoholic fatty liver disease and other metabolic conditions in Guatemala

Abstract: Background Previous studies have suggested an association between Helicobacter pylori (H pylori) and nonalcoholic fatty liver disease (NAFLD). The aim of the current study was to examine the association in Guatemala, a region with elevated prevalences of both H pylori and NAFLD. Associations between H pylori and other metabolic conditions were also examined, as were associations between H hepaticus and H bilis and the metabolic conditions. Materials & Methods The analysis included 424 participants from a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Due to its cost-effectiveness and non-invasiveness, the serology test is a common method used in the health screening center which is conducted as routine blood sampling. In addition, as various Hp antigens are associated differently with metabolic conditions, it would be better to verify multiple Hp antigen using multiplex serology [ 44 ], however, it was unavailable in this study. Also, we did not have information of Hp eradication history.…”
Section: Limitationsmentioning
confidence: 99%
“…Due to its cost-effectiveness and non-invasiveness, the serology test is a common method used in the health screening center which is conducted as routine blood sampling. In addition, as various Hp antigens are associated differently with metabolic conditions, it would be better to verify multiple Hp antigen using multiplex serology [ 44 ], however, it was unavailable in this study. Also, we did not have information of Hp eradication history.…”
Section: Limitationsmentioning
confidence: 99%
“…19 Thus, the variation in the presence of HP virulence is proposed to affect the severity of NASH. 14 The decrement of FBS was more significant in HP eradicated participants than the controls in this investigation. This outcome is in parallel with the previous studies, which showed glycemic improvement after HP eradication in participants with diabetes mellitus type 2.…”
Section: Discussionmentioning
confidence: 48%
“…13 On the other hand, some studies showed no association between HP and NASH. 14,15 The discrepancy seen in the current pieces of evidence may stem from several reasons. First, serum aminotransferase levels fluctuate in the course of NASH, thus, measuring these markers at a single time point might not reliably predict the inflammatory status of the disease.…”
Section: Discussionmentioning
confidence: 90%
“…Another cross-sectional study of 2051 Chinese asymptomatic adults found no relationship between H. pylori infection and NAFLD (31). Other studies based on Korean (32,33), American (34) and Guatemalan (35) population also showed that H. pylori infection was not associated with NAFLD.…”
Section: Introductionmentioning
confidence: 93%